Analisis Komparasi Efektivitas Model Kooperatif Tipe Two Stay Two Stray (TSTS) dengan Jigsaw Pada Mata Pelajaran Informatika di sekolah Menengah - Abna Hidayati; Vevi Sunarti; Novra Arina (Jurnal Family Education, 2023)
The cooperative learning learning model essentially functions to increase cooperation and collaboration between students. There are many types of cooperative learning. This type will be effective if used according to the characteristics and content of learning. The problem in the field is that many teachers choose the wrong learning model so that learning outcomes do not reach the KKM. This study aims to analyze the effectiveness of the cooperative model in informatics learning. The research method is quantitative with a quasy experimental type. The population is high school students with a total of 380 people. Samples were taken purposively, namely based on the similarity of student characteristics and learning outcomes that had been obtained previously. The research procedure is divided into two classes, namely control and experiment. Data were processed by differential statistical analysis using differential analysis (t test).